THE ROLE OF PARENTAL RELATIONSHIP IN THE STATEMENT OF INDEPENDENT OPINIONS IN ADOLESCENT CHILDREN - Abdullaeva Nigora Raximovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the statement of independent opinions in adolescent children, the significance of the relationship between parents was analyzed. Proposals were developed on the basis of the conclusions drawn.